Present status of potential medicinal plants grown in mattuvil, jaffna - Sathiyaseelan, V. (University of Jaffna, 2012)
Medicinal plants are widely utilized in both the developing and developed countries. In the developing countries herbal medicines form the backbone of the traditional therapeutic armoury. The objective of the study is to determine the presence of potential medicinal plants grown in Mattuvil that are used in traditional medicine. The Mattuvil area map was used to locate and count the medicinal plants and to group them based on morphological characters and nature of plant parts used in traditional medicine. The pH of the soil at Mattuvil was 8.4, which was found suitable for different medicinal plants. A total of 145 species of medicinal plants were recorded. This comprises perennials (75%), annual (23%) and biennials (2%). Eight percent poisonous plants were also recorded at Mattuvil. Out of 145 plants, 19 used for diabetic mellitus, 8 in vatha diseases and 10 in treating skin diseases, and 12 for respiratory disorders. Further, grouping based on morphology revealed herbs (39%), trees (32%), shrubs (14%), climbers (11%), lianas (1%), creepers (1%), cacti (1%) and holo parasites (1%). Based on the usage of plant parts the plant species were grouped as whole plants (30), leaves (64), seeds (23), flowers (19), young pods (12), fruits (19), roots (33), root barks (28), stems (4), barks (6), rhizomes (3), gums (3) and galls (3). Out of 145 plant species, 10% were spinaches. In addition, medicinal plants recommended in Pararaja Sekaram (1929), a Jaffna Siddha text, for traditional medicine, namely Erythroxylum monogynum, Mallotus philippensis, Plecospermum spinosum, Azima tetracantha, Canavalia ensiformis, Hugonia mystax, Scutia indica and Pisonia aculeata were also found growing at Mattuvil. These results revealed grouping of the valuable and potential medicinal plants used in indigenous medicine into different categories and this information will help to conserve and promote cultivation of medicinal plants at Mattuvil and dissemination of knowledge on the existence of medicinal plants among indigenous practioners and the residents of Mattuvil. These results will proclaim Mattuvil as a protective zone for valuable medicinal plants.
Keywords: Mattuvil; Medicinal plants; Present status; Traditional medicine